AGR453: Agribusiness Marketing / Faculty of Plantation and Agrotechnology - UiTM, Faculty of Plantation and Agrotechnology (Universiti Teknologi MARA (UiTM), 2020)
This course deals with understanding and analysis of managing risk, opportunities and strategies, planning, marketing mix, distribution channel, implementing new technologies, international trade, marketing local commodities and case studies of agriculture and the applications of agro-technology.